Assessment of ship impact risk to offshore structures - New NORSOK N-003 guidelines. (January 2019) - Moan, Torgeir; Amdahl, Jørgen; Ersdal, Gerhard
Abstract: The regulatory requirements for the Norwegian Continental Shelf specify that ship impact actions and other accidental actions should be determined by risk assessment. However, when the first requirements on collision energy from supply vessels were introduced by DNV around 1980, the frequency of impacts by attendant vessels were high – of the order of 10 −3 per installation year. Therefore, it was assumed in the initial requirements that the impact action associated with attendant vessels should, as a minimum, be calculated for the maximum authorized vessel assumed to service the installation. At that time the resulting minimum impact energies were 11 and 14 MJ for head on and side impact, respectively; and have remained the same since then. However, the supply vessel size has since increased and design of supply ship bow and platform has changed. Further, the use of DP controlled supply vessels has increased, which may imply larger velocities at impact. Moreover, the consequence of ship impacts might change e.g. due to the change in design of supply vessels by providing ice-strengthened bows in supply vessels and platforms with cantilevered decks. In the revision of the NORSOK N-003 standard on "Actions and action effects" the requirements to ship impacts are being reassessed and updated based on statistics on supply vessel sizes and collision energies; as well on service experiences. Besides revisiting the requirements to attendant vessels, other ship impact scenarios are also considered. This especially includes the collision risk associated with shuttle tanker – FPSO. This paper presents the background for the revised standard; in terms of ship impact actions relating especially to supply vessels and shuttle tankers, recognising that the main risk control relating to ship impact is to limit the probability of impacts by operational control. Moreover, the consequences in terms of damage for different types of platforms are addressed, by e.g. demonstrating the feasibility of satisfying more restrictive requirements and especially the effect of providing ice-strengthened bows in supply vessels and designing platforms with cantilevered decks. Highlights: Robustness criterion in terms of Accidental Collapse Limit State. Establish a risk based ship impact criterion in the revised NORSOK N-003 standard. Focus on impacts by attendant vessels and FPSOs in tandem offloading. Establish a procedure for design against ship impacts. Assessment of the implication of minimum impact energy requirements for various types of platforms. It is shown that it might be feasible to carry out a strength design of impacted components to prevent progressive failure.